2000
DOI: 10.1523/jneurosci.20-13-04809.2000
|View full text |Cite
|
Sign up to set email alerts
|

Altered Stress-Induced Anxiety in Adenylyl Cyclase Type VIII-Deficient Mice

Abstract: Stress results in alterations in behavior and physiology that can be either adaptive or maladaptive. To define the molecular pathways involved in the response to stress further, we generated mice deficient (KO) in the calcium-stimulated adenylyl cyclase type VIII (AC8) by homologous recombination in embryonic stem cells. AC8 KO mice demonstrate a compromise in calcium-stimulated AC activity in the hippocampus, hypothalamus, thalamus, and brainstem. Hippocampal slices derived from AC8 KO mice fail to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 59 publications
4
116
0
Order By: Relevance
“…4b) between FBGRKO and control mice in this test (n ϭ 10). The similar activity between control and FBGRKO mice in this open-field measure is consistent with our previous analysis of general locomotor activity under basal conditions using beam breaks in a photocell apparatus (Schaefer et al, 2000;Boyle et al, 2005). Thus, the FBGRKO mice are not hyperactive in general.…”
Section: Locomotor Activation In the Elevated Plus Mazesupporting
confidence: 90%
“…4b) between FBGRKO and control mice in this test (n ϭ 10). The similar activity between control and FBGRKO mice in this open-field measure is consistent with our previous analysis of general locomotor activity under basal conditions using beam breaks in a photocell apparatus (Schaefer et al, 2000;Boyle et al, 2005). Thus, the FBGRKO mice are not hyperactive in general.…”
Section: Locomotor Activation In the Elevated Plus Mazesupporting
confidence: 90%
“…It has been shown that expression of specific isoforms, subcellular localization, and differential regulation of ACs greatly contribute to the diverse and tissue-specific regulation of cAMP (33)(34)(35)(36)(37). Here we report a novel regulatory pathway for control of cAMP synthesis in three hematopoietic cell lines.…”
Section: Discussionmentioning
confidence: 90%
“…Although mice deficient in either mAC VIII or G␣ olf are fertile but rarely surviving (43,44), homozygous matings of mAC III K.O. mice were unproductive, although they showed normal mounting and anogenital sniffing behaviors (45).…”
Section: Discussionmentioning
confidence: 99%